Pemetaan Daerah Rawan Longsor di Kota Ternate, Indonesia Menggunakan Sistem Informasi Geografis - Rakuasa, Heinrich; Khromykh, Vadim V.; Rifai, Ahmat (PT. Pubsains Nur Cendekia, 2025)
Landslides seriously threaten safety and sustainable development in Ternate City, Indonesia, due to tectonic activity, steep topography, high rainfall, and urbanization pressure. This study aims to map landslide-prone areas using Geographic Information System and the weighted overlay method by integrating seven parameters: elevation, slope, soil type, geology, land use, rainfall, and distance from active faults. The analysis results show that slopes >40% and areas near active faults have the highest risk. Based on the total area of 10,162 ha, 51% (5,197 ha) is classified as a high-risk zone, 31% (3,123 ha) as medium risk, and 18% (1,842 ha) as low risk. These findings emphasize the need for risk-zoning-based mitigation priorities, such as strengthening spatial planning policies, building disaster-resistant infrastructure, and educating communities. This research not only provides a scientific basis for development planning and disaster risk reduction in Ternate but also provides a methodological framework that can be adapted in other landslide-prone areas, especially in volcanic island regions with similar geographical conditions.